Border control reinterpreted: collective memory and the narrative self - Gyollai, Daniel (Critical criminology, 2022)
This article explores the potential of historical narratives to inform and guide action, taking the case of border control in Hungary. The Hungarian government has recently criminalised irregular border crossing and made a comparison between the Ottoman Occupation and contemporary challenges of mass migration to legitimise its new measures. Qualitative interviews conducted in 2019 seem to suggest that some members of the border police, consciously or unconsciously, have drawn from this narrative repertoire to make sense of their own role in border control. Drawing on the concept of the narrative self, the article outlines how the collective memory of the Ottoman conquest may have shaped the understanding of mass migration and the self-interpretation of those involved in border control.